Implementation of the Concept of State According to Abu Al-A'la Al-Maududi in Indonesia - Mohamad Latief; Faza Islami (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
The relationship between religion and politics cannot be separated, both are related to each other. Because in politics requires religious values so that a person can find the essence of politics and can be responsible for his mandate to society and God. Therefore, Abu al-A'la al-Maududi offers a concept in the state in accordance with Islamic provisions, when sovereignty in the state is in the hands of God (theodemocracy). The concept is different from the West when the sovereignty of the state is in the hands of the people (democracy). Both concepts have pros and cons in their application, so there are countries like Indonesia that are predominantly Muslim but use western concepts. Whether the concept will be relevant in Indonesia or not.? This discussion will use a qualitative method by processing discussions from primary and secondary sources and then analyzing between the concept of the state owned by Abu al-A'la al-Maududi and the western concept and its implementation in Indonesia. Therefore, the purpose of this discussion is to examine the concept of the state according to Abu al-A'la al-Maududi in Indonesia.